Diospyros adinandrifolia, a new species of Ebenaceae from Yunnan, China - Liu, Qun; Zou, Chun-Yu; Yang, Chong; Chen, Wen-Hong; Lyu, Ling; Zhang, Gui-Liang; Shui, Yu-Min; Zhang, Zhi-Xiang (Phytotaxa, 2024)
Diospyros adinandrifolia, a new species of Diospyros (Ebenaceae) from southeast Yunnan, China, is described and photographed. Photographs of type specimens and ecological information are provided. Diospyros adinandrifolia resembles D. undulata in its elliptic leaves, clustered flowers, and synsepalous calyces, but differs by abaxial leaf base without glands, calyx without obvious lobes and the fruiting calyx being not reflexed during maturation. It is also morphologically similar to D. dussaudii in buds shape and inflorescence morphology, but differs in its leaves being white pubescent when young and glabrescent, paniculate male inflorescences, and succulent fruit. Based on the examination of the specimens from China and Vietnam, the species is categorized as Endangered (EN) according to the IUCN Red List criteria.